Conceptualizing digital literacies and digital ethics for sustainability education. Issue 3 (7th July 2014) - Brown, Susan A.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to discuss the need for integrating a focus on digital literacies and digital ethics into sustainability education, proposing a conceptualization of these for sustainability education. Design/methodology/approach – The paper draws on relevant literature in the field of sustainability education and in the field of digital literacies and digital ethics. It synthesizes perspectives in both fields to form a conceptualization of digital literacies and digital ethics for sustainability education. Findings – The paper conceptualizes "digital literacies" as a capacity to reflect on the nature of digital space in relation to sustainability challenges and "digital ethics" as a capacity to reflexively engage with digital space in ways which build rich discourses around sustainability. Critically reflective and exploratory activities in digital space are a means of developing these capacities. Originality/value – The conceptualization allows sustainability education to account for the increased role digital space plays in shaping views of sustainability challenges. It proposes a pedagogical approach to doing this.